Review of on-Street Parking Scenario of Motijheel Commercial Area (Dainik Bangla to Shapla Square) - Mahfuza Akter; Taslima Akter; Aktaruzzaman; Abu Hussain (Journal of Bangladesh Institute of Planners, 2013)
Parking problem is one of the burning issues in transport study for any commercial and business area. Efficient movements of vehicle as well as usages of surrounding lands are greatly affected by provision of parking. Motijheel, the CBD of Dhaka has been experiencing an upsurge of parking demand over the last few decades. To investigate the present on- street parking condition of Motijheel area a study consists of parking inventory survey and parking usage survey by patrol has been conducted from Dainik Bangla to Shapla Square. This study has revealed that overall demand is 2.73 times greater than available supply. Relatively longer duration of parking is mainly responsible for this. To get a more detailed overview different parking considerations like parking accumulation, parking index, parking duration, turnover, spill over etc are also calculated. On the basis of survey and analyses, some recommendations have been provided to improve the situation. Journal of Bangladesh Institute of Planners, Vol. 6, Dec 2013, pp. 173-180